Peningkatan Hasil Belajar Pengukuran Sudut dengan Pendekatan Pendidikan Matematika Realistik Indonesia (PMRI) - Purba, Rabiatul Adawiyah; Rahmatina, Rahmatina (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2017)
The research is aimed to know about the improvement of learning outcomes angular measurements with the indonesian realistic mathematics education approach (pmri) at fourth grade in public elementary school 02 Percontohan in Bukittinggi City. This research is kind of action research and using qualitative and quantitative approach. Subject of the research is all fourth grade B. Instrument of the research used test sheet and observation sheet. Data analysis technique of the research used to qualitative and quantitative descriptive. So that, it can be concluded that with a realistic mathematics education approach (PMRI) can be improvement of learning outcomes angular measurements the student.